Synthesis and Antimicrobial Activity of Some New Substituted Quinoxalines - El-Atawy, Mohamed A. (Molecules, 2019)
A number of new symmetrically and asymmetrically 2,3-disubstituted quinoxalines were synthesized through functionalization of 2,3-dichloroquinoxaline (2,3-DCQ) with a variety of sulfur and/or nitrogen nucleophiles. The structures of the obtained compounds were established based on their spectral data and elemental analysis. The antimicrobial activity for the prepared compounds was investigated against four bacterial species and two fungal strains. The symmetrically disubstituted quinoxalines 2, 3, 4, and 5 displayed the most significant antibacterial activity, while compounds 6a, 6b, and the pentacyclic compound 10 showed considerable antifungal activity. Furthermore, compounds 3f, 6b showed broad antimicrobial spectrum against most of the tested strains.